Child Support Enforcement and Infants Health Outcomes - Koirala, Niraj Prasad (Journal of Social Economics Research, 2021)
This paper explores the potential externality of enforcements in child support policies on infants’ health outcomes. Exploiting the variations in child support policies across states and over the year and using the universe of birth records in the US (1975-2004), I document that the policies were effective in improving birth outcomes. Infants born to single mothers in states that fully adopt child support policies have on average 38 grams higher birth weight and 99 basis points lower likelihood of being born with low birth weight. These effects hold for a wide range of health outcomes. The marginal impacts are larger for mothers in states above-median changes in child support policies and for mothers who reside in poorer states. The results suggest that a higher quantity of prenatal care and better timing of prenatal care could be possible mechanisms of impact. This study contributes to the existing literature by providing the first evidence of health externality of child support policies for infants’ health outcomes.